2012
DOI: 10.1089/ten.tea.2011.0467
|View full text |Cite
|
Sign up to set email alerts
|

Cotransplantation of Adipose-Derived Mesenchymal Stromal Cells and Endothelial Cells in a Modular Construct Drives Vascularization in SCID/bg Mice

Abstract: A modular approach to adipose tissue engineering was explored by embedding adipose-derived mesenchymal stromal cells (adMSC) in sub-mm-sized collagen rods or ''modules'' and coating with human microvascular endothelial cells (HMEC). After subcutaneous injection into a SCID/Bg mouse, HMEC on modules containing embedded adMSC appeared to detach from the modules to form vessels as early as day 3, as confirmed by the human EC-specific UEA-1 lectin stain, and these vessels persisted for up to 90 days. Vessel number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 54 publications
(69 reference statements)
1
45
1
Order By: Relevance
“…These vessels develop in several days after injection and stably integrate into host vasculature. 9,23,24 The formation of stable vessels is a complex process requiring finely orchestrated interactions between 2 cell types, EC and mural/pericyte cells, and the surrounding environment. Previously, to facilitate mechanistic analysis of EC-ASC interactions, we introduced an in vitro model of cocultivation of human EC and ASC in a system containing serum but no additional exogenous cytokines or extracellular matrix.…”
Section: Editorial See P 752 In This Issue See P 751mentioning
confidence: 99%
“…These vessels develop in several days after injection and stably integrate into host vasculature. 9,23,24 The formation of stable vessels is a complex process requiring finely orchestrated interactions between 2 cell types, EC and mural/pericyte cells, and the surrounding environment. Previously, to facilitate mechanistic analysis of EC-ASC interactions, we introduced an in vitro model of cocultivation of human EC and ASC in a system containing serum but no additional exogenous cytokines or extracellular matrix.…”
Section: Editorial See P 752 In This Issue See P 751mentioning
confidence: 99%
“…In the SCID/bg mouse, blood vessels did not form without the co-implantation of MSC, which become pericyte support cells and there was little ECM deposited as the implanted tissue remodeled. 12,22 However, in a immunosuppressed rat model, implantation of EC alone formed blood vessels which persisted for long periods of time but were leaky, and there was more granulation tissue that formed as the tissue remodeled. 15 The addition of MSC to the implanted tissue decreased the leakiness of the newly formed vessels.…”
Section: Hypoxia Drives the Recruitment Of Local Cells To The Tissue mentioning
confidence: 99%
“…21,33 Both top-down and bottom-up approaches have been exploited, using various combinations of cells, growth factors and biomaterials. We have focused on modular tissue engineering, 12,15,16,22 in which several thousand (for rodents) individual microtissues are injected in a space filling manner. In this method the EC form a network after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…16 As a consequence of collagen's strong cell adhesive properties, the surface of collagen modules can be seeded with endothelial cells (ECs) to enhance vascularization. 17 Previous reports in rats 17,18 and SCID/bg mice 19 have demonstrated that this EC coverage leads to the formation of vessel-like structures which can integrate into the host's vascular system. This vasculature is expected not only to ensure the adequate oxygenation of the cells within the tissue construct but in this context to also facilitate the entry of the EOC-derived anti-fibrotic factors into the host's circulation.…”
Section: Introductionmentioning
confidence: 96%